Строение пищеварительной системы клеща Varroa jacobsoni — паразита медоносной пчелы - Акимов, И.А.; Старовир, И.С. (Вестник зоологии, 1983)
Description of morphology, topography and histological peculiarities of digestive system and Malpighian tubules in a parasitic mile, Varroa jacobsoni. Functional morphology changes in the midgut intestine epithelium and Malpighian tubules epithelium during mite female repletion and starvation are shown. Morpho-functional types of the intestine and Malpighian tubules cells are designated. 1t is established that parasitic specialization in Varroa is not connected with considerable morpho-functional changes in digestive system as compared to predaceous mites.